Investigation of iron passivity in highly alkaline media using reactive-force field molecular dynamics. (15th August 2019) - DorMohammadi, Hossein; Pang, Qin; Murkute, Pratik; Árnadóttir, Líney; Burkan Isgor, O.
Graphical abstract: Highlights: Passivity or iron in 0.3 M NaOH solution (pH = 13.5) was studied using Reax FF-MD. Passivation initiated with the formation of an Fe(OH)2 layer on the metal surface. Fe(OH)2 formation allowed oxygen diffusion without excessive iron dissolution. Passive film had multiple layers: Fe2 O3 (outer), Fe3 O4 (middle) and FeO (inner). XPS investigation showed that Fe III /Fe II ratio decreased with increasing film depth. Abstract: The passivity of Fe(110) in a 0.316 M NaOH solution (pH = 13.5) was investigated using Reactive Force Field Molecular Dynamics. The initial stages of passivation involved the formation of Fe(OH)2 species on the metal surface, which created conditions for oxygen diffusion into the metal without iron dissolution into the electrolyte. The passive film had multiple oxide structures: Fe2 O3 in outer layers, Fe3 O4 in the middle layers, and FeO in the innermost layers. A parallel XPS investigation showed that the Fe III /Fe II ratio decreased with increasing film depth and confirmed the findings of the ReaxFF-MD simulations.